Investing to Mitigate and Adapt to Climate Change : A Framework Model - Bonen, Anthony (IMF Working Papers; Working Paper ;, 2016)
We propose a macroeconomic model to assess optimal public policy decisions in the the face of competing funding demands for climate change action versus traditional welfare-enhancing capital investment. How to properly delineate the costs and benefits of traditional versus adaption-focused development remains an open question. The paper places particular emphasis on the changing level of risk and vulnerabilities faced by developing countries as they allocate investment toward growth strategies, adapting to climate change and emissions mitigation.